An Economic Analysis of Drug Offences in Thailand : Exploring the relationship between drug offences and economic costs - Kyaw, Yoon Nandar; Htike, Zin Me; Wang, Ruyi; Li, Jiaxian (Jejaring Penelitian dan Pengabdian Masyarakat, 2025)
Thailand faces significant hurdles in combating drug offenses, with more than 74% of itsjail population incarcerated for drug related crimes. Methamphetamine (‘ya ba’)dominated these cases, highlighting the widespread problem of addiction and trafficking.Despite a tripling of government investment on prevention, suppression, and treatmentinitiatives between 2006 and 2016, the public’s understanding of drug laws, rehabilitationchoices, and health dangers remains uncle/ar. The 2021 Narcotics Code contained health-related improvements, such as voluntary treatment and partial decriminalization,indicating a trend towards a more balanced approach. However, these interventions havehad little effect on decreasing systemic burdens and societal stigmas. A comprehensiveplan that includes education, accessible rehabilitation, socioeconomic support, andcompassionate laws is required to reduce the economic and social consequences of drug-related offenses